Sophomore Students’ Voice of Web-Based Learning English. - Butarbutar, Ranta; Sauhenda, Angla Florensy; Arfiani, Arfiani; Pure, Ermelinda Agnes Gunu (JEELS (Journal of English Education and Linguistics Studies), 2024)
The present study aims to bridge the gaps between limited Web-based Learning English (WBLE) focused on speaking ability enhancement and sophomore multilevel speaking students' perceptions and to design a qualitative narrative study using seven sophomore university students aged 20-24 years old. Students were chosen through purposive sampling and used mobile phones and personal computers for learning purposes. The results demonstrated the use of web-based language learning to encourage students to speak English as a Foreign Language. The students used two WBLE techniques, online and offline, both on- and off-campus. They accessed five recommended WBLE: British Broadcasting Corporation, PhraseMix, VOA Learning English, British Council, and TalkEnglish. Students used online WBLE to attend blended lectures agreed upon by their teachers. This study highlights the potential of WBLE to improve speaking skills among sophomore-level students, emphasizing the need for further research and development in this field.